Effect of air pollution, air pressure and air temperature on new onset pulmonary thromboembolism: A case-control study - Akgül, Engin; Yümün, Gündüz (Journal of Surgery and Medicine, 2020)
Aim: Air pollution affects many people globally and there are allegations and studies that it leads to serious health problems, such as pulmonary thromboembolism. In this study, we investigated the possible relationship between air conditions and pulmonary thromboembolism. Methods: This study was carried out by archive scanning. Patients with acute dyspnea who were shown to have PE by contrast-enhanced CT were included in the analysis. Patients with a history of trauma, malignancy, recent surgical intervention, or immobility were excluded from the study. On the day of complaints, Particulate matter 10 (PM10), sulfur dioxide (SO2), air temperature and air pressure values were obtained online from the relevant institution of Environment and Urban Ministry. These 215 patients’ data were then evaluated statistically. Results: Results suggest that the incidence of pulmonary embolism was higher on days when PM10 (P<0.001) and air pressure levels were high (P<0.001). However, SO2 and temperature were not directly associated with the frequency of pulmonary embolism (P=0.422, P=0.778). Conclusion: In light of this study, it can be said that air quality may have different consequences on human health. Elevated PM10 and air pressure levels can affect the circulatory system negatively and aggravate thromboembolism.